The contribution of subjective wellbeing to the improvement of the academic performance of university students through time management as a mediator factor: A structural equation modeling - Hicham KHABBACHE; Abdelhalim CHERQUI; Khalid OUAZIZI; Driss AIT ALI; Zakaria ABIDLI; Abdelaziz ALLIOUI; Joumana ELTURK; Mahmood BAHRAMIZADEH; Murat YILDIRIM; Nicola Luigi BRAGAZZI; Gabriella NUCERA; Lukasz SZARPAK; et al. (Journal of Health and Social Sciences)
Introduction: In recent years, there has been a growing focus on assessing life satisfaction among students, as a way of measuring their overall wellbeing. This study aims to investigate how positive feelings (PF) and negative feelings (NF) predict academic performance (AP) through time management (TM) as a mediator in this process. Methods: This cross-sectional study was conducted among Moroccan students from the University of Sidi Mohamed ben Abdullah in Fez. A total of 540 students (288 females, 53.3%; 252 males, 46.7%; with a mean age of 21.51 and a standard deviation of 3.86) completed a pencil and paper questionnaire. A questionnaire was adopted as a tool in this research. Positive emotions (Pe), Negative emotions (Ne), and Life satisfaction were measured on a five-rank scale for each variable (strongly agree = 5, strongly disagree = 1). Results: The results of using structural equation modeling showed that the life satisfaction factor, which includes two dimensions, PF and NF, has a significant influence on academic performance. Discussion: Creating a supportive and positive learning environment can enhance students' wellbeing and improve academic performance.